Overview of accessibility and quality of antiepileptic drugs in Madagascar. (October 2016) - Nizard, Mandy; Jost, Jérémy; Tanamasoandro, Rakotovao; Andriambololona, Rindra; Megherbi, Mehdi; Solofomalala, Gaetan Duval; Marquet, Pierre; Preux, Pierre-Marie; Ratsimbazafy, Voa
Highlights: The Haute Matsiatra district is well served with health infrastructure. People with epilepsy do not consider themselves sick but believed they are "possessed". The most prescribed antiepileptic drug is phenobarbital. The antiepileptic drugs are globally of good quality. Abstract: Purpose: To determine the accessibility of treatment and the quality of antiepileptic drugs (AEDs) in the Haute Matsiatra district of Madagascar. Methods: Cross-sectional descriptive study and interviews. Samples of 10 units of each available AED were collected, and the active ingredient was quantified by reversed-phase high-performance liquid chromatography (RP-HPLC) with photodiode-array UV detection. The quality of an AED was considered satisfactory if the quantity of active ingredient in each tablet was in the range ±15% of the average value according to the European Pharmacopeia (6th edition, 2008). Results: The area was well served with health infrastructure but rescue facilities were poorly distributed. Available AEDs were all first-generation, and 73% were generic formulations. People with epilepsy (PWE) surveyed consulted traditional healers and most were treated with plants. PWE did not consider themselves sick but believed they were "possessed"; they consulted a doctor only immediately after a seizure, following the advice of traditional healers. The most prescribed AED was phenobarbital, costing between 0.03 and 0.12 US Dollar (US$) per 100 mg. The purchase of full treatment was difficult for 77% of PWE and as a result, 39% took nothing. The quality of AEDs were considered unsatisfactory in 2.8% of cases. Conclusion: The AEDs collected in Haute Matsiatra were globally of good quality. The main limiting elements were a lack of knowledge among PWE that epilepsy is a disease, and the cost of traditional treatments.